An Insight into Biodegradable Polymers and their Biomedical Applications for Wound Healing - Halder, Tripti; Barot, Harshit; Kumar, Bhavna; Kaushik, Vishakha; Patel, Hiren; Bhut, Hastik; Saha, Bijit; Poddar, Sibani; Acharya, Niyati (Current Pharmaceutical Design, 2024)
Biodegradable polymers, encompassing both natural and synthetic polymers, have demonstrated efficacy as carriers for synthetic drugs, natural bioactive molecules, and inorganic metals. This is due to their ability to control the release of these substances. As a result, various advanced materials, such as nanoparticle-loaded hydrogels, nanofibrous scaffolds, and nanocomposites, have been developed. These materials have shown promise in enhancing processes, such as cell proliferation, vascular angiogenesis, hair growth, and wound healing management. Natural polymers, including hyaluronic acid, collagen, chitosan, gelatin, and alginate, as well as synthetic polymers like polylactic acid, polyglycolic acid, polylactic co-glycolic acid, and PCA, have significant potential for promoting wound healing. This study examines the advancements in biodegradable polymers for wound healing, specifically focusing on each polymer and its distinctive formulations. It also discusses the in vitro experiments conducted using different cell lines, as well as the in vivo studies that explore the numerous uses of these polymers in wound healing. The discussion also included the exploration of modifications or combinations of several polymers, as well as surface changes, in order to produce synergistic effects and address the limitations of individual polymers. The goal was to expedite the healing process of different chronic wounds. Due to this, there have been notable advancements in the technological use of polymeric mixes, including biodegradable polymer-based scaffolds, which have accelerated the process of wound healing.
Keywords: hyaluronic acid